Ligands selectively tune the local and global motions of neurotensin receptor 1 (NTS1) - Fabian Bumbak; Miquel Pons; Asuka Inoue; Juan Carlos Paniagua; Fei Yan; Hongwei Wu; Scott A. Robson; Ross A.D. Bathgate; Daniel J. Scott; Paul R. Gooley; Joshua J. Ziarek (Cell Reports, 2023)
Summary: Nuclear magnetic resonance (NMR) studies have revealed that fast methyl sidechain dynamics can report on entropically-driven allostery. Yet, NMR applications have been largely limited to the super-microsecond motional regimes of G protein-coupled receptors (GPCRs). We use 13Cε-methionine chemical shift-based global order parameters to test if ligands affect the fast dynamics of a thermostabilized GPCR, neurotensin receptor 1 (NTS1). We establish that the NTS1 solution ensemble includes substates with lifetimes on several, discrete timescales. The longest-lived states reflect those captured in agonist- and inverse agonist-bound crystal structures, separated by large energy barriers. We observe that the rapid fluctuations of individual methionine residues, superimposed on these long-lived states, respond collectively with the degree of fast, global dynamics correlating with ligand pharmacology. This approach lends confidence to interpreting spectra in terms of local structure and methyl dihedral angle geometry. The results suggest a role for sub-microsecond dynamics and conformational entropy in GPCR ligand discrimination.